Pengembangan Modul Literasi Numerasi dalam Penguatan P5 - Noviyanti, Ni Wayan Mia Noviyanti; Sueca, I Nengah (Lentera: Jurnal Ilmiah Kependidikan, 2024)
Literacy and Numeracy skills are essential for enhancing students' capabilities across various fields. Based on this premise, the study aimed to develop a Literacy and Numeracy Module tailored to the needs of Astika Dharma students, who primarily excel in physical and non-academic areas. This research employed a Research & Development (R&D) approach, which involved assessing (Research) the needs of Astika Dharma students and subsequently creating (Develop) a Literacy and Numeracy Module aligned with these needs. An initial analysis was conducted through a Pre-Test involving 26 student representatives from each class. The module content focuses on Literacy and Numeracy topics relevant to students' daily lives. As a result, the developed module meets the specific needs of the students, presenting engaging material that addresses common issues faced by students in both their school and community environments.